We’re Here, You Just Don’t Know How to Reach Us: Conducting Research with Citizens on the Socio-Economic Margins - M. Tanya Brann-Barrett (Adult Education Research Conference, 2007)
In this paper, methodological challenges that emerged when conducting research with socially and economically disadvantaged young adults in a semi-rural community are examined. Recruitment and retention issues related to ethics protocols, trust, and economic disadvantage are addressed. Strategies governing bodies can employ to support research with difficult to reach populations are suggested.